MENINGKATKAN MUTU NILAI KEMANUSIAAN PADA ANAK-ANAK MELALUI SATUA MEN TIWAS TEKEN MEN SUGIH (SEBUAH KAJIAN SEMIOTIKA) - Pradnya Paramitha, Ni Made Ayu Susanthi (LPM IHDN Denpasar, 2020)
There is one way to form a child?s character is with a tale or a story where in Balinese life we called satua or masatua. Satua is a part of lisan literary once as a work of grain Graine literature, unattached to the temple and rhythm as well. Although satua is as one of the local obscension wisdom of the ancestral legacy and has been there for a long time, but this is still relevant to be used as one of the tools in developing way of life, personality, characteristics and a wisdom for people in Bali and of course based on the rule as a Balinese in the community. One of the best example of the satua called ?Men Tiwas Teken Men Sugih? or the life between the poor and the rich. By using semiotic Peirce approach, and through the way of life from the poor family in the character, this article would emphasise a moral message regarding the behavior of the decreators. By this means that we can take an example to educate the young children what is the meaning of life and also to increase the quality of humanity to child